Pencapaian Ranah Afektif Self-Efficacy Peserta Didik Sekolah Dasar pada Implementasi Model Pembelajaran Discovery Learning - Zahratuz Zakiah; Yanti Fitria (Universitas Negeri Padang, 2023)
This study is motivated by the affective aspect of students' self-efficacy which is not high enough. The purpose of this research is to describe the achievement of affective aspects of students' self-efficacy in the implementation of the Discovery Learning model. The hypothesis of this research is that there is an achievement of the affective aspects of students' self-efficacy. This study used the Quasy Experimental Design method using the nonequivalent pretest-posttest control group design. Data collection techniques through self-efficacy questionnaires and final tests. The data analysis technique is the N-Gain test, t-test and regression test. The test results show that: The N-Gain test for the experimental class is 0.314 in the medium category and the control class is 0.197 in the low category. T-test = 8.437 > t-table = 2.014 with an achievement of 77.6%. There is an achievement of student self-efficacy in the implementation of the Discovery Learning model, this can be applied at the beginning of students entering school.